Estado penal e a prisão como negócio: a expansão do sistema prisional no Espírito Santo (2009 - 2019) - Moura, Kamila Vieira de (2023)
The present work is a documentary research, with the theme "Criminal State and the prison as a business: the expansion of the prison system in Espírito Santo (2009- 2019), whose qualitative research aims to analyze and problematize the expansion of the Prison System Prison in Espírito Santo since 2009, as an institutional response to the tragic period known as “capixaba dungeons”. To this end, a brief historical context of economic policies from the 20th century onwards is presented, which aims to direct readers to understand the path of transformations of capital until its arrival in the contemporary neoliberal branch. In continuity, the logic of the Penal State as a result of the neoliberal ideal is also approached, from the perspective of the sociologist researcher Loic Wacquant. It also goes into the history, characteristics and data of the Brazilian Prison System, with emphasis on the scenario of the state of Espírito Santo at the height of its second penitentiary crisis. And, finally, the research shows the response of the State Government, presenting fundamentals that put it in question as to its business character. The results culminate in exorbitant data regarding the amounts invested through bids and contracts during this period, without the state apparatus corresponding to the two main objectives: reducing overcrowding and implementing the prison's resocializing capacity.